Model Graph Untuk Penataan Sistem Transpormasi Berbasis Algoritma Travelsal Dan MST - Nur Halizzah; Muhammad Yoga; Muhammad Zidane Al - Kahfi; Muhammad Rosidhin (Jurnal Sains Informatika Terapan, 2025)
In order to connect important places with the least amount of travel time and operating expense, an effective urban transportation system needs to have well-planned routes. With a case study on the Trans Batam bus system in Indonesia, this paper introduces a graph-based model for organizing transportation networks utilizing traversal algorithms and the Minimum Spanning Tree (MST) technique. Each node in this model denotes a bus stop or an important hub for activity, and the edges show potential routes between them, weighted by variables like distance, expected journey time, or road conditions..Depth-First Search (DFS) and Breadth-First Search (BFS) are two traversal algorithms that are used to map and investigate the entire set of possible pathways within the network. The most effective connection paths that connect all stops with the least cumulative weight and no cycles are then found using MST algorithms like Kruskal or Prim. The model's ability to eliminate redundant routes, identify the shortest routes, and provide affordable options for route optimization and corridor expansion is demonstrated by simulation and analysis.The results suggest that this graph-based planning framework offers a practical and adaptive solution for improving public transportation efficiency. It may serve as a valuable reference for transportation authorities and urban planners seeking to optimize mass transit systems in rapidly growing cities like Batam.